Design of Cooling and Monitoring Electric Motorbike Batteries Based On Internet of Things (IoT) - Dhito, Anaga Ozthandrick De Dhito; Amalia, Zakiyah (International Journal of Frontier Technology and Engineering, 2024)
The temperature increase in the battery occurs when the battery is used and charged. This increase in temperature will have a negative impact on the battery, such as reducing battery life, and can even cause the battery to explode. The objective of this research is to design a cooling device with a fan in the form of a fan and equipped with monitoring the condition of electric motorbike batteries using the Blynk application on a smartphone. The research method used in this research is an experimental method with the independent variable in the form of cooling fan rotation speed using PWM with a Duty Cycle of 25% (slow), 50% (medium), and 100% (fast) and charging current variations of 4A and 6A. Testing was carried out on a LiFePO4 battery pack, with a constant battery capacity of 10% and charging up to 100%. Temperature and battery charging time are identified as dependent variables whose values ​​are influenced by the independent variables. The results of this research show that variations in cooling fan rotation speed and variations in charging current have an effect on charging time and battery temperature. The higher the fan rotation speed, the more stable the battery temperature rise when charging. When the fan rotation speed is slow the temperature reaches 37.5°C, while when the fan rotation speed is fast the temperature is 32.04°C. The greater the charging current, the shorter the charging time. When charging the battery capacity to 10% - 100%, a 4A charging current takes 4004.11 seconds, while a 6A charging current takes 2893 seconds. Each increase in battery capacity during charging shows a significant change in temperature, where the average difference in temperature from variations in 4A and 6A charging currents is 1.07°C.